History of Malaysia - Fathil, Fauziah (2018)
The lecture/presentation is meant to equip volunteers who work as tour guide at National Museum Malaysia, Kuala Lumpur with knowledge of the history of Malaysia. The lecture covers from the Malacca Sultanate era in the 15th - 16th century until contemporary period.